THE IMPACT OF THE INVESTMENT ENVIRONMENT ON ECONOMIC DEVELOPMENT - Yu. M. Khasanova (American Journals, 2025)
The article highlights the advantages of using investments in the development of the country’s economy, as well as approaches related to extended multifactor and risk-oriented investment, and issues related to indicators of investment activity at the enterprise level.
Keywords: Investment, investment advantages, extended multifactor approach, risk, evaluation indicators.